PENGEMBANGAN BAHAN AJAR BERBASIS COMPUTER ASSISTED INSTRUCTION (CAI) PADA POKOK BAHASAN GERAK HARMONIS SEDERHANA DI SMA - Sepdiana Widya Rahmawati; Sri Wahyuni; Pramudya Dwi Aristya Putra (JURNAL PEMBELAJARAN FISIKA, 2017)
Technology development effect included in education field especially physics. In learning process, technology presented as teaching materials based on computer assisted instruction. This learning materials included many media as picture, graphic, animation, text, video, and physics theory especially simple harmonic motion in one product. This article was the result of development research of physics teaching materials based on computer assisted instruction on topic simple harmonic motion. Computer assisted instruction based teaching materials in this research used tutorial type. The purpose of this research were to describe validity of CAI based teaching materials, student’s response, and student’s learning result. The techniques of data collection were test, observation, interviews and documentation. The Result of this research were CAI based teaching materials on topic simple harmonic motion was valid with point 4.23, this learning materials had positive response in learning process for topic simple harmonic motion with percentage of agreement 79% and students’learning result is high with score 77. Keywords: Computer Assisted Instruction (CAI), Learning Result, Students’ response.